Biện pháp quản lí hoạt động giáo dục hành vi giao tiếp văn hoá cho học sinh ở các trường tiểu học thành phố Hà Nội theo tiếp cận phối hợp - Bùi, Thị Nên (Tạp chí Giáo dục, 2024)
Educating cultural communication behavior plays an important role in the comprehensive development of primary school students, contributing to creating a favorable environment for teaching and educational activities. To improve the effectiveness of educating students on cultural communication behavior, the management of this activity needs to be paid attention to in primary schools. Based on the theory and practice of managing cultural communication behavior education activities for students in primary schools in Hanoi city, the article proposes a number of educational management measures. Cultural communication behavior for students at primary schools in the research area according to a coordinated approach. Implementing these measures helps mobilize resources and ensure effectiveness in managing cultural communication behavior education for students in primary schools in Hanoi.